2008
DOI: 10.1080/10408390701540124
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder (ADHD) and Obesity: A Systematic Review of the Literature

Abstract: Purpose of review To systematically review the literature on the prevalence and pharmacological treatment of ADHD in looked-after children (LAC). Recent findings LAC are a very challenging population from a clinical and psychosocial standpoint, with higher mental health needs compared to non LAC. To date, no systematic review on the prevalence of ADHD, and its treatment, in LAC is available. Summary We searched Pubmed, PsycInfo EMBASE + EMBASE CLASSIC, OVID Medline and Web of Science up to November 9 th, 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
180
5
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(209 citation statements)
references
References 74 publications
13
180
5
11
Order By: Relevance
“…5 These behaviors may predispose them to bullying involvement, and impulsivity and inhibition problems have also been linked to overeating and overweight. 29 Contrary to our hypothesis, children with overweight had risks of bullying involvement similar to those of their normal-weight counterparts. This similarity has been observed previously in studies of secondary school and higher grades in primary school.…”
Section: Discussioncontrasting
confidence: 53%
“…5 These behaviors may predispose them to bullying involvement, and impulsivity and inhibition problems have also been linked to overeating and overweight. 29 Contrary to our hypothesis, children with overweight had risks of bullying involvement similar to those of their normal-weight counterparts. This similarity has been observed previously in studies of secondary school and higher grades in primary school.…”
Section: Discussioncontrasting
confidence: 53%
“…Maternal educational level was, for example, positively associated with healthy food choices, being physically active and restriction of sedentary time. 55 BMI Adult (parental) BMI and ADHD 43 and ADHD symptoms 30,56 are epidemiologically associated. ADHD is highly heritable 51 through both genetic and shared environmental influences.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature (Cortese et al, 2008) concluded that samples of obese children referred for obesity treatment present with a higher than expected prevalence of ADHD. Additionally, although the data were limited, all studies included indicated that subjects with ADHD were heavier than expected.…”
Section: Attention Defi Cit Hyperactivity Disorder (Adhd) In Obese Chmentioning
confidence: 99%